2006
DOI: 10.1186/1471-2105-7-442
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to combine multiple molecular biomarkers for dichotomous diagnostic classification

Abstract: Background: In spite of the recognized diagnostic potential of biomarkers, the quest for squelching noise and wringing in information from a given set of biomarkers continues. Here, we suggest a statistical algorithm that -assuming each molecular biomarker to be a diagnostic testenriches the diagnostic performance of an optimized set of independent biomarkers employing established statistical techniques. We validated the proposed algorithm using several simulation datasets in addition to four publicly availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 69 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…To assess the complementary performance of the potential glycan biomarkers in Table 3, a composite score was derived using multivariate logistic regression [7173]. First, the abundance of each glycan in each sample was normalized so that low- and high-abundance glycans would be weighted equally.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the complementary performance of the potential glycan biomarkers in Table 3, a composite score was derived using multivariate logistic regression [7173]. First, the abundance of each glycan in each sample was normalized so that low- and high-abundance glycans would be weighted equally.…”
Section: Resultsmentioning
confidence: 99%
“…From the number of glycopeptide markers found and the AUC values, it can be expected that the glycosite Asn241 present in GP3 is most associated with gastric cancer. To complement and improve the sensitivity and specificity of the markers, we applied a logistic regression model to potential biomarkers and calculated a combined ROC curve [ 57 , 58 , 59 ]. The AUC improved significantly to 0.950 (GP1), 0.929 (GP2), and 0.977 (GP3), respectively ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…WHR was reported to be a better predictor in a number of countries (14)(15)(16)(17). Also, WC was reported to show superiority over other anthropometric measures in the prediction of type 2 diabetes in British women (18), U.S. men (19), German women (11), and Indian men and women (20). On the other hand, other studies demonstrated that BMI, WHR, WC, and WHtR had similar predictive powers for the risk of type 2 diabetes (24).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable controversy still exists as to which measure most accurately defines body fat distribution. Studies from different countries and ethnicities in the world showed that anthropometric measures have different predictive powers for diabetes and hypertension (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Therefore, the predictive power of anthropometric measures and their appropriate cut-off points should be established for different ethnicities.…”
Section: Introductionmentioning
confidence: 99%